A high elastic shoe material and its preparation process
By using thermoplastic polyurethane elastomers and other auxiliary components in the sole material, combining composite antibacterial agents and functionalized nanosilicon dioxide and other components, and using a blend foaming process, the problem of insufficient antibacterial performance of existing sole materials is solved, and shoe materials with high elasticity and versatility are prepared.
Patent Information
- Application Number
- CN202411830229.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing sole materials have shortcomings in antibacterial properties, and poor dispersion during the preparation process, which affects other properties.
Thermoplastic polyurethane elastomer is used as the main component, combined with auxiliary components such as ethylene-vinyl acetate copolymer, ethylene-octene copolymer, nitrile rubber, etc., and added composite antibacterial agents, functionalized nanosilica and zinc oxide to prepare high-elastic shoe materials through blending and foaming process.
The prepared shoe materials not only have high elasticity and good antibacterial properties, but also have strength, wear resistance, yellowing resistance and flame retardancy, meeting the market's demand for high-quality and versatile sole materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of shoe materials, and in particular relates to a high-elastic shoe material and a preparation process thereof. Background Art
[0002] Thermoplastic elastomers have the characteristics of both rubber and thermoplastic plastics. They show high elasticity of rubber at room temperature and can be plasticized and formed into polymer materials at high temperature. They have the excellent properties of high elasticity, aging resistance and oil resistance of traditional cross-linked vulcanized rubber, and at the same time have the characteristics of convenient processing and wide processing methods of ordinary plastics. Thermoplastic elastomers mainly include polystyrene thermoplastic elastomers, polyolefin thermoplastic elastomers, polyurethane thermoplastic elastomers, polyether thermoplastic elastomers, etc. Among them, thermoplastic polyurethane elastomers have the advantages of low density, soft texture, good dimensional stability, long storage life, good shock absorption and anti-slip properties, good temperature resistance and chemical resistance, etc., and are widely used in the fields of outer soles, midsoles, heels, toes, insoles, etc. of various types of shoes. At present, people are increasingly pursuing higher quality and more versatile shoes, and have higher and higher requirements on the performance and functionality of shoe sole materials, especially sole materials with antibacterial properties, which are crucial to prevent bacteria from breeding in foot sweat and endangering the health of human foot skin.
[0003] A Chinese patent application with application number 202310999182.7 discloses a highly elastic antibacterial foamed shoe material and a preparation method thereof. The raw materials of the foamed shoe material include thermoplastic elastic composite ultra-light elastomer, thermoplastic polyurethane elastomer rubber, antibacterial masterbatch, antioxidant, bubble stabilizer, inorganic aerogel, and foaming aid. The antibacterial masterbatch is prepared by mixing and granulating silica, nano zinc oxide particles, nano copper oxide particles, dispersant, coupling agent, deionized water, and silicone resin. The antibacterial masterbatch and the combination of alum solve the problems of poor antibacterial property and poor antibacterial durability of the shoe material. However, the main antibacterial component is inorganic raw material, which has poor dispersibility during the preparation process and poor compatibility with the organic raw material of the polymer elastomer, which can easily affect other properties of the shoe material.
[0004] Chinese patent application number 202311565950.4 discloses a highly elastic, environmentally friendly, lightweight and comfortable foamed sole and a preparation method thereof. The foamed sole is foamed from a composite resin consisting of polylactic acid, TPU resin, foaming agent, antioxidant and filler, wherein the filler is compounded from bagasse, rice husk and seaweed. By selecting a compound of thermoglucosidic Bacillus and thermoflavour Amycolatopsis, the cellulose in bagasse, rice husk and seaweed is decomposed to a certain extent, so that the active components in bagasse, rice husk and seaweed are analyzed out. The prepared filler contains a composite plant extract, so that the filler achieves an antibacterial effect, but the content of the antibacterial component in the filler is limited, resulting in insufficient antibacterial performance of the foamed sole.
[0005] Therefore, it is urgent to develop multifunctional sole materials with excellent antibacterial properties to meet market demand. Summary of the invention
[0006] The purpose of the present invention is to provide a high-elastic shoe material and a preparation process thereof in view of the deficiencies in the prior art. The shoe material prepared by the present invention has moderate hardness, light weight, high elasticity, and also has good strength, wear resistance, yellowing resistance, antibacterial property and flame retardancy.
[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0008] A high-elastic shoe material comprises the following components in parts by weight: 70-80 parts of thermoplastic polyurethane elastomer; 10-20 parts of ethylene-vinyl acetate copolymer; 15-20 parts of ethylene-octene copolymer; 10-15 parts of nitrile rubber; 8-10 parts of composite antibacterial agent; 2-4 parts of foaming agent; 0.6-1 part of zinc oxide; 1-2 parts of antioxidant; and 10-15 parts of composite filler.
[0009] Furthermore, the composite filler is composed of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:1-2;
[0010] Furthermore, the foaming agent is azodicarbonamide; the antioxidant is any one of antioxidant 5057, antioxidant 1135, and antioxidant 1010, or a mixture of several of them.
[0011] In the technical scheme of the present invention, the preparation method of the composite antibacterial agent is: add carboxymethyl chitosan to 50-60wt% ethanol, add a modified compound and triethylamine, heat to 70-80°C, stir and react for 5-6h, after the reaction is completed, adjust the pH to neutral with dilute hydrochloric acid, precipitate with acetone, filter, wash the solid with acetone, and dry to obtain the composite antibacterial agent.
[0012] Furthermore, the mass ratio of the carboxymethyl chitosan, the modified compound and the triethylamine is 1:0.2-0.3:0.05-0.1.
[0013] In the technical solution of the present invention, the preparation method of functionalized nano-silicon dioxide is:
[0014] 1) Add nano-silica to 60-70wt% ethanol, disperse evenly with ultrasound, add 3-aminopropyltriethoxysilane dropwise, raise the temperature to 50-60°C, stir and react for 1-2h, centrifuge after the reaction is complete, wash the solid with ethanol, and dry to obtain amino-modified nano-silica;
[0015] 2) Add the amino-modified nano-silica to ethanol, disperse it evenly by ultrasonication, add the modified compound and triethylamine, raise the temperature to 65-70°C, stir and react for 4-5 hours, centrifuge after the reaction is completed, wash the solid with ethanol, and dry to obtain the functionalized nano-silica.
[0016] Furthermore, in step 1), the mass ratio of nano-silica to 3-aminopropyltriethoxysilane is 10:0.3-0.5.
[0017] Furthermore, in step 2), the mass ratio of the amino-modified nano-silica, compound 3, and triethylamine is 10:0.5-0.6:0.1-0.2.
[0018] In the technical solution of the present invention, the preparation method of the modified compound is:
[0019] S1. Add 6-chloro-1-hydroxybenzotriazole and dodecyldimethyl tertiary amine in a molar ratio of 1:1.0-1.1 to ethanol, reflux for 12-14 hours, detect the completion of the reaction by TLC, remove ethanol by rotary evaporation, extract with ethyl acetate and water, and concentrate the aqueous phase under reduced pressure to obtain compound 1. Compound 1 is:
[0020]
[0021] S2, according to the molar ratio of compound 1, epichlorohydrin and triethylamine of 1:1.0-1.1:1.3-1.5, first add compound 1 and triethylamine to chloroform, then add epichlorohydrin dropwise, after the addition is complete, heat to 50-60°C, react for 4-5h, detect the completion of the reaction by TLC, remove chloroform by rotary evaporation, extract with ethyl acetate and water, and concentrate the aqueous phase under reduced pressure to obtain compound 2, which is:
[0022]
[0023] S3, according to the molar ratio of compound 2, diethylphosphite chloride and triethylamine of 1:1.0-1.1:1.3-1.5, first add compound 2 and triethylamine to anhydrous ether, then add diethylphosphite chloride dropwise under ice bath condition, after the addition is complete, keep warm for 2-3h, detect the completion of the reaction by TLC, remove anhydrous ether by rotary evaporation, extract with ethyl acetate and water, and concentrate the aqueous phase under reduced pressure to obtain a modified compound, the modified compound is:
[0024]
[0025] The present invention provides a preparation process of a high-elastic shoe material, which is characterized by comprising the following steps:
[0026] a. Add thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, ethylene-octene copolymer and nitrile rubber into an internal mixer according to the mass ratio, and mix at 160-170° C. for 5-8 minutes to obtain a premix;
[0027] b. Add the composite antibacterial agent, foaming agent, zinc oxide, antioxidant and composite filler to the premix obtained in step a, and knead at 140-150° C. for 3-5 min to obtain a mixture;
[0028] c. Granulate the mixture obtained in step b, put it into a mold for foaming, and obtain a high-elastic shoe material.
[0029] Furthermore, the foaming conditions in step c are: foaming for 30-40 minutes at 10-15 MPa and 170-180°C.
[0030] The present invention also provides application of the above-mentioned high-elastic shoe material in shoe soles.
[0031] The present invention has the following beneficial effects:
[0032] 1. The present invention uses 6-chloro-1-hydroxybenzotriazole as a raw material, and reacts with dodecyldimethyl tertiary amine, epichlorohydrin, and diethylphosphite chloride in sequence to synthesize a modified compound containing a long-chain quaternary ammonium salt group with antibacterial and dispersing effects, a benzotriazole group that absorbs ultraviolet light, and a phosphate group with a flame retardant effect in the structure. The modified compound prepared by the present invention has antibacterial, dispersing and flame retardant effects, and can also be used as an anti-ultraviolet absorber, which can convert ultraviolet light into visible light such as blue light, green light, and yellow light, thereby preventing the material from aging due to ultraviolet rays.
[0033] 2. In order to improve the antibacterial and flame retardant properties of footwear materials, the present invention grafts the modified compound onto the carboxymethyl chitosan molecular chain with antibacterial effect on the one hand, and grafts the modified compound onto the surface of nano-silica on the other hand, thereby obtaining a composite antibacterial agent and functionalized nano-silica with dual antibacterial effects. The presence of the modified compound gives the composite antibacterial agent and the functional nano-silica good antibacterial properties, photostability and flame retardancy. The composite antibacterial agent and the functional nano-silica can work synergistically to help improve the good yellowing resistance, antibacterial properties and flame retardancy of the high-elastic footwear materials. In combination with antioxidants, the yellowing resistance of the footwear materials is further improved. In addition, the functional nano-silica has good dispersibility and compatibility in other organic components, which can not only improve the strength of the footwear materials, but also can be combined with ethylene-octene copolymers to jointly improve the wear resistance of the footwear materials.
[0034] 3. The present invention uses thermoplastic polyurethane elastomer as a main component, ethylene-vinyl acetate copolymer, ethylene-octene copolymer, and nitrile rubber as auxiliary components, adds a composite antibacterial agent, an antioxidant, a composite filler composed of talcum powder and functionalized nano-silicon dioxide, a foaming agent, and zinc oxide, and obtains a shoe material with moderate hardness, light weight, and high elasticity through a blending foaming process. The shoe material obtained by the present invention also has good hardness, strength, wear resistance, yellowing resistance, antibacterial property, and flame retardancy. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] In the technical solution of the present invention, the chemical reagents used are all commercially available, among which the thermoplastic polyurethane elastomer is selected from Bayer 8792A-S043 of Germany; the ethylene-vinyl acetate copolymer is selected from DuPont 150 of the United States; the ethylene-octene copolymer is selected from Dow 8150 of the United States; the nitrile rubber is selected from nitrile rubber powder SH3003; azodicarbonamide CAS No. 123-77-3; zinc oxide CAS No. 1314-13-2; talc CAS No. 14807-96-6; antioxidant 5057 CAS No. 68411-46-1; antioxidant 1135 CAS No. 125643-61-0; antioxidant CAS No. 1010 6683-19-8; carboxymethyl chitosan CAS No. 83512-85-0 (viscosity average molecular weight is 5.0×10 3 , deacetylation degree is 90%, carboxymethylation is 80%); 6-chloro-1-hydroxybenzotriazole CAS No. 26198-19-6; dodecyl dimethyl tertiary amine CAS No. 112-18-5; epichlorohydrin CAS No. 106-89-8; triethylamine CAS No. 121-44-8; diethylphosphite chloride CAS No. 589-57-1; 3-aminopropyltrimethoxysilane CAS No. 13822-56-5.
[0037] In the technical solution of the present invention, the preparation method of the modified compound is:
[0038] S1. 17.0 g of 6-chloro-1-hydroxybenzotriazole and 23.5 g of dodecyldimethyl tertiary amine in a molar ratio of 1:1.1 were added to 500 mL of ethanol, and the mixture was refluxed for 13 h. The reaction was completed by TLC detection. The ethanol was removed by rotary evaporation, and the mixture was extracted with ethyl acetate and water. The aqueous phase was concentrated under reduced pressure to obtain 31.8 g of compound 1. The reaction process was as follows:
[0039]
[0040] Compound 1: ESI (m / z): 383.9 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 12.30 (s, 1H), 7.86 (d, J=8.6Hz, 1H), 7.70 (s, 1H), 7.14 (d, J=8.6H z, 1H), 3.74 (s, 6H), 3.22-3.25 (m, 2H), 1.73-1.75 (m, 2H), 1.26-1.29 (m, 18H), 0.88-0.91 (m, 3H).
[0041] S2, according to the molar ratio of compound 1, epichlorohydrin and triethylamine of 1:1.1:1.3, first add 30.0g of compound 1 and 10.3g of triethylamine to 400mL of chloroform, then add 8.0g of epichlorohydrin dropwise, after the addition is complete, heat to 60°C, react for 5h, detect the completion of the reaction by TLC, remove chloroform by rotary evaporation, extract with ethyl acetate and water, and concentrate the aqueous phase under reduced pressure to obtain 30.5g of compound 2. The reaction process is:
[0042]
[0043] Compound 2: ESI (m / z): 476.5 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 7.88 (d, J=8.6Hz, 1H), 7.71 (s, 1H), 7.16 (d, J=8.6Hz, 1H), 5.37 (s, 1H), 3.75- 3.80 (m, 9H), 3.42-3.47 (m, 2H), 3.22-3.25 (m, 2H), 1.72-1.75 (m, 2H), 1.26-1.29 (m, 18H), 0.88-0.90 (m, 3H).
[0044] S3, according to the molar ratio of compound 2, diethylphosphite chloride and triethylamine of 1:1.1:1.5, first add 25.0g of compound 2 and 7.9g of triethylamine to 500mL of anhydrous ether, and then add 9.1g of diethylphosphite chloride dropwise under ice bath condition. After the addition is complete, keep warm for 3h. The reaction is completed by TLC detection, and the anhydrous ether is removed by rotary evaporation. The product is extracted with ethyl acetate and water, and the aqueous phase is concentrated under reduced pressure to obtain 27.2g of the modified compound. The reaction process is:
[0045]
[0046] Modified compound: ESI (m / z): 596.5 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 7.87 (d, J=8.6Hz, 1H), 7.70 (s, 1H), 7.15 (d, J=8.6Hz, 1H), 3.76-3.83 (m , 13H), 3.44-3.49 (m, 2H), 3.23-3.25 (m, 2H), 1.72-1.74 (m, 2H), 1.25-1.29 (m, 24H), 0.88-0.90 (m, 3H).
[0047] A high-elastic shoe material comprises the following components in parts by weight: 80 parts of thermoplastic polyurethane elastomer; 15 parts of ethylene-vinyl acetate copolymer; 20 parts of ethylene-octene copolymer; 10 parts of nitrile rubber; 10 parts of composite antibacterial agent; 4 parts of foaming agent; 1 part of zinc oxide; 1.5 parts of antioxidant; 15 parts of composite filler; the composite filler consists of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:2; the foaming agent is azodicarbonamide; and the antioxidant is antioxidant 5057.
[0048] The preparation method of the composite antibacterial agent is as follows: carboxymethyl chitosan is added to 60wt% ethanol, a modified compound and triethylamine are added, the temperature is raised to 80°C, and the reaction is stirred for 5 hours. After the reaction is completed, the pH is adjusted to neutral with dilute hydrochloric acid, acetone is precipitated, filtered, the solid is washed with acetone, and dried to obtain the composite antibacterial agent; the mass ratio of carboxymethyl chitosan, the modified compound, and triethylamine is 1:0.3:0.1.
[0049] The preparation method of functionalized nano-silica is:
[0050] 1) Add nano-silica to 70wt% ethanol, disperse evenly by ultrasonication, add 3-aminopropyltriethoxysilane dropwise, raise the temperature to 60°C, stir and react for 1.5h, centrifuge after the reaction is complete, wash the solid with ethanol, and dry to obtain amino-modified nano-silica, the mass ratio of nano-silica to 3-aminopropyltriethoxysilane is 10:0.5; the amount of 70wt% ethanol is 20 times the mass of nano-silica;
[0051] 2) Add the amino-modified nano-silica to ethanol, disperse it evenly by ultrasonication, add the modified compound and triethylamine, heat to 65°C, stir and react for 5 hours, centrifuge after the reaction is completed, wash the solid with ethanol, and dry to obtain functionalized nano-silica; the mass ratio of the amino-modified nano-silica, compound 3, and triethylamine is 10:0.6:0.2; the amount of ethanol is 20 times the mass of the amino-modified nano-silica.
[0052] A preparation process of a high-elastic shoe material comprises the following steps:
[0053] a. Add thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, ethylene-octene copolymer and nitrile rubber into an internal mixer according to the mass ratio, and mix at 170° C. for 7 minutes to obtain a premix;
[0054] b. Adding the composite antibacterial agent, foaming agent, zinc oxide, antioxidant and composite filler to the premix obtained in step a, and kneading at 150° C. for 5 min to obtain a mixture;
[0055] c. Granulate the mixture obtained in step b, put it into a mold, and foam it at 15 MPa and 180° C. for 30 minutes to obtain a high-elastic shoe material.
[0056] A high-elastic shoe material comprises the following components in parts by weight: 75 parts of thermoplastic polyurethane elastomer; 20 parts of ethylene-vinyl acetate copolymer; 18 parts of ethylene-octene copolymer; 15 parts of nitrile rubber; 9 parts of composite antibacterial agent; 3 parts of foaming agent; 0.8 parts of zinc oxide; 2 parts of antioxidant; 12 parts of composite filler; the composite filler consists of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:1.5; the foaming agent is azodicarbonamide; and the antioxidant is antioxidant 1135.
[0057] The preparation method of the composite antibacterial agent is as follows: add carboxymethyl chitosan to 50wt% ethanol, add a modified compound and triethylamine, heat to 70°C, stir and react for 5.5h, after the reaction is completed, adjust the pH to neutral with dilute hydrochloric acid, precipitate with acetone, filter, wash the solid with acetone, and dry to obtain the composite antibacterial agent; the mass ratio of carboxymethyl chitosan, modified compound and triethylamine is 1:0.25:0.05.
[0058] The preparation method of functionalized nano-silica is:
[0059] 1) Add nano-silica to 60wt% ethanol, disperse evenly by ultrasonication, add 3-aminopropyltriethoxysilane dropwise, raise the temperature to 50°C, stir and react for 2h, centrifuge after the reaction is completed, wash the solid with ethanol, and dry to obtain amino-modified nano-silica, the mass ratio of nano-silica to 3-aminopropyltriethoxysilane is 10:0.4; the amount of 60wt% ethanol is 20 times the mass of nano-silica;
[0060] 2) Add the amino-modified nano-silica to ethanol, disperse it evenly by ultrasonication, add the modified compound and triethylamine, heat to 70°C, stir and react for 4.5 hours. After the reaction is completed, centrifuge, wash the solid with ethanol, and dry to obtain functionalized nano-silica; the mass ratio of the amino-modified nano-silica, compound 3, and triethylamine is 10:0.5:0.15; the amount of ethanol is 20 times the mass of the amino-modified nano-silica.
[0061] A preparation process of a high-elastic shoe material comprises the following steps:
[0062] a. Add thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, ethylene-octene copolymer and nitrile rubber into an internal mixer according to the mass ratio, and mix at 165° C. for 5 minutes to obtain a premix;
[0063] b. Add the composite antibacterial agent, foaming agent, zinc oxide, antioxidant and composite filler to the premix obtained in step a, and knead at 140° C. for 4 min to obtain a mixture;
[0064] c. Granulate the mixture obtained in step b, put it into a mold, and foam it at 10 MPa and 170° C. for 40 minutes to obtain a high-elastic shoe material.
[0065] A high-elastic shoe material comprises the following components in parts by weight: 70 parts of thermoplastic polyurethane elastomer; 10 parts of ethylene-vinyl acetate copolymer; 15 parts of ethylene-octene copolymer; 12 parts of nitrile rubber; 8 parts of composite antibacterial agent; 2 parts of foaming agent; 0.6 parts of zinc oxide; 1 part of antioxidant; 10 parts of composite filler; the composite filler consists of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:1; the foaming agent is azodicarbonamide; and the antioxidant is antioxidant 1010.
[0066] The preparation method of the composite antibacterial agent is as follows: add carboxymethyl chitosan to 55wt% ethanol, add a modified compound and triethylamine, heat to 75°C, stir and react for 6 hours, after the reaction is completed, adjust the pH to neutral with dilute hydrochloric acid, precipitate with acetone, filter, wash the solid with acetone, and dry to obtain the composite antibacterial agent; the mass ratio of carboxymethyl chitosan, modified compound and triethylamine is 1:0.2:0.08.
[0067] The preparation method of functionalized nano-silica is:
[0068] 1) Add nano-silica to 65wt% ethanol, disperse evenly by ultrasonication, add 3-aminopropyltriethoxysilane dropwise, raise the temperature to 55°C, stir and react for 1h, centrifuge after the reaction is complete, wash the solid with ethanol, and dry to obtain amino nano-silica, the mass ratio of nano-silica to 3-aminopropyltriethoxysilane is 10:0.3; the amount of 65wt% ethanol is 20 times the mass of nano-silica;
[0069] 2) Add the amino-modified nano-silica to ethanol, disperse it evenly by ultrasonication, add the modified compound and triethylamine, heat to 65°C, stir and react for 4 hours, centrifuge after the reaction is completed, wash the solid with ethanol, and dry to obtain functionalized nano-silica; the mass ratio of the amino-modified nano-silica, compound 3, and triethylamine is 10:0.55:0.1; the amount of ethanol is 20 times the mass of the amino-modified nano-silica.
[0070] A preparation process of a high-elastic shoe material comprises the following steps:
[0071] a. Add thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, ethylene-octene copolymer and nitrile rubber into an internal mixer according to the mass ratio, and mix at 160° C. for 8 minutes to obtain a premix;
[0072] b. Add the composite antibacterial agent, foaming agent, zinc oxide, antioxidant and composite filler to the premix obtained in step a, and knead at 145° C. for 3 min to obtain a mixture;
[0073] c. Granulate the mixture obtained in step b, put it into a mold, and foam it at 13 MPa and 175° C. for 35 minutes to obtain a high-elastic shoe material.
[0074] A high-elastic shoe material comprises the following components in parts by weight: 80 parts of thermoplastic polyurethane elastomer; 20 parts of ethylene-vinyl acetate copolymer; 15 parts of ethylene-octene copolymer; 13 parts of nitrile rubber; 9 parts of composite antibacterial agent; 3 parts of foaming agent; 0.7 parts of zinc oxide; 2 parts of antioxidant; 13 parts of composite filler; the composite filler consists of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:1.5; the foaming agent is azodicarbonamide; and the antioxidant is antioxidant 1010.
[0075] The preparation method of the composite antibacterial agent is the same as that in Example 1.
[0076] The preparation method of functionalized nano-silica is:
[0077] 1) Same as step 1) in Example 1;
[0078] 2) Same as step 2) in Example 1.
[0079] A preparation process of a high-elastic shoe material comprises the following steps:
[0080] a. Add thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, ethylene-octene copolymer and nitrile rubber into an internal mixer according to the mass ratio, and mix at 170° C. for 8 minutes to obtain a premix;
[0081] b. Add the composite antibacterial agent, foaming agent, zinc oxide, antioxidant and composite filler to the premix obtained in step a, and knead at 150° C. for 3 min to obtain a mixture;
[0082] c. Granulate the mixture obtained in step b, put it into a mold, and foam it at 10 MPa and 180° C. for 30 minutes to obtain a high-elastic shoe material.
[0083] Comparative Example 1
[0084] Compared with Example 1, the composite antibacterial agent in this comparative example is only carboxymethyl chitosan.
[0085] A high-elastic shoe material comprises the following components in parts by weight: 80 parts of thermoplastic polyurethane elastomer; 15 parts of ethylene-vinyl acetate copolymer; 20 parts of ethylene-octene copolymer; 10 parts of nitrile rubber; 10 parts of composite antibacterial agent; 4 parts of foaming agent; 1 part of zinc oxide; 1.5 parts of antioxidant; 15 parts of composite filler; the composite filler consists of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:2; the foaming agent is azodicarbonamide; the antioxidant is antioxidant 5057; and the composite antibacterial agent is carboxymethyl chitosan.
[0086] The preparation method of functionalized nano-silica and the preparation process of high elastic shoe material are the same as those in Example 1.
[0087] Comparative Example 2
[0088] Compared with Example 1, the composite filler in this comparative example consists of talcum powder and nano-silicon dioxide in a mass ratio of 1:2.
[0089] A high-elastic shoe material comprises the following components in parts by weight: 80 parts of thermoplastic polyurethane elastomer; 15 parts of ethylene-vinyl acetate copolymer; 20 parts of ethylene-octene copolymer; 10 parts of nitrile rubber; 10 parts of composite antibacterial agent; 4 parts of foaming agent; 1 part of zinc oxide; 1.5 parts of antioxidant; 15 parts of composite filler; the composite filler consists of talcum powder and nano silicon dioxide in a mass ratio of 1:2; the foaming agent is azodicarbonamide; and the antioxidant is antioxidant 5057.
[0090] The preparation method of the composite antibacterial agent is the same as that in Example 1.
[0091] The preparation process of a high elastic shoe material is the same as that in Example 1.
[0092] Comparative Example 3
[0093] Compared with Example 1, the composite antibacterial agent in this comparative example is only carboxymethyl chitosan, and the composite filler is composed of talcum powder and nano-silicon dioxide in a mass ratio of 1:2.
[0094] A high-elastic shoe material comprises the following components in parts by weight: 80 parts of thermoplastic polyurethane elastomer; 15 parts of ethylene-vinyl acetate copolymer; 20 parts of ethylene-octene copolymer; 10 parts of nitrile rubber; 10 parts of composite antibacterial agent; 4 parts of foaming agent; 1 part of zinc oxide; 1.5 parts of antioxidant; 15 parts of composite filler; the composite filler consists of talcum powder and nano silicon dioxide in a mass ratio of 1:2; the foaming agent is azodicarbonamide; the antioxidant is antioxidant 5057; and the composite antibacterial agent is carboxymethyl chitosan.
[0095] The preparation process of a high elastic shoe material is the same as that in Example 1.
[0096] Related performance tests
[0097] The performance tests of the high elastic shoe materials prepared in Examples 1-4 and Comparative Examples 1-3 were conducted, wherein the hardness was measured according to GB / T3903.4-2008; the density was measured according to GB / T 533-2008; the tensile strength and elongation at break were measured according to GB / T 8948-2008; the elasticity was measured according to ASTM D2632; the wear resistance was measured according to GB / T 9867-2008; the yellowing resistance (UV lamp) was measured according to HG / T 3689-2014; the antibacterial performance was measured according to HG / T3663-2014; the flame retardant performance was measured by the limiting oxygen index method; the results are shown in Table 1 below.
[0098] Table 1 Performance test results of high elastic shoe materials
[0099]
[0100] It can be seen from the results in Table 1 that the high elastic shoe materials prepared in Examples 1-4 of the present invention have excellent comprehensive properties, moderate hardness, light weight, high elasticity, and good strength, wear resistance, yellowing resistance, antibacterial and flame retardancy. Compared with Comparative Examples 1-3, the composite antibacterial agent used in Example 1 of the present invention is carboxymethyl chitosan grafted with a modified compound, and the composite filler is talcum powder and functional nano-silica grafted with a modified compound; and the modified compound structure contains a long-chain quaternary ammonium salt group with antibacterial and dispersing effects, a benzotriazole group that absorbs ultraviolet light, and a barrier The phosphate groups with flame retardancy endow the composite antibacterial agent and functional nano-silica with good antibacterial, light stability and flame retardancy. The composite antibacterial agent and functional nano-silica can work synergistically to help improve the good yellowing resistance, antibacterial and flame retardancy of high-elasticity footwear materials. In combination with antioxidants, the yellowing resistance of footwear materials is further improved. In addition, the functional nano-silica has good dispersibility and compatibility in other organic components, which can not only improve the strength of the footwear materials, but also can be combined with ethylene-octene copolymers to jointly improve the wear resistance of the footwear materials.
[0101] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0102] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A high elastic shoe material, characterized in that: The invention comprises the following components in parts by weight: 70-80 parts of thermoplastic polyurethane elastomer; 10-20 parts of ethylene-vinyl acetate copolymer; 15-20 parts of ethylene-octene copolymer; 10-15 parts of nitrile rubber; 8-10 parts of composite antibacterial agent; 2-4 parts of foaming agent; 0.6-1 parts of zinc oxide; 1-2 parts of antioxidant; 10-15 parts of composite filler; the composite filler is composed of talcum powder and functionalized nano-silicon dioxide in a mass ratio of 1:1-2; The preparation method of the composite antibacterial agent is as follows: adding carboxymethyl chitosan to 50-60wt% ethanol, adding a modified compound and triethylamine, heating to 70-80°C, stirring for reaction for 5-6h, and after the reaction is completed, adjusting the pH to neutral with dilute hydrochloric acid, precipitating with acetone, filtering, washing the solid with acetone, and drying to obtain the composite antibacterial agent; The preparation method of the functionalized nano-silicon dioxide is as follows: 1) Add nano-silica to 60-70wt% ethanol, disperse evenly with ultrasound, add 3-aminopropyltriethoxysilane dropwise, raise the temperature to 50-60°C, stir and react for 1-2h, centrifuge after the reaction is complete, wash the solid with ethanol, and dry to obtain amino-modified nano-silica; 2) Add the amino-modified nano-silica to ethanol, disperse it evenly by ultrasonication, add the modified compound and triethylamine, raise the temperature to 65-70°C, stir and react for 4-5 hours, centrifuge after the reaction is completed, wash the solid with ethanol, and dry it to obtain the functionalized nano-silica; The modified compounds in step 2) and the preparation method of the composite antibacterial agent are: .
2. A highly elastic shoe material according to claim 1, characterized in that: The mass ratio of nano-silicon dioxide to 3-aminopropyltriethoxysilane in step 1) is 10:0.3-0.
5.
3. The high elastic shoe material according to claim 1, characterized in that: In step 2), the mass ratio of the amino-modified nano-silica, the modified compound and the triethylamine is 10:0.5-0.6:0.1-0.
2.
4. The high elastic shoe material according to claim 1, characterized in that: The preparation method of the modified compound is: S1. Add 6-chloro-1-hydroxybenzotriazole and dodecyldimethylamine in a molar ratio of 1:1.0-1.1 to ethanol, reflux for 12-14 hours, detect the completion of the reaction by TLC, remove ethanol by rotary evaporation, extract with ethyl acetate and water, and concentrate the aqueous phase under reduced pressure to obtain compound 1; S2, first add compound 1 and triethylamine to chloroform according to the molar ratio of compound 1, epichlorohydrin and triethylamine of 1:1.0-1.1:1.3-1.5, then add epichlorohydrin dropwise, after the addition is complete, heat to 50-60°C, react for 4-5h, detect the completion of the reaction by TLC, remove chloroform by rotary evaporation, extract with ethyl acetate and water, and concentrate the aqueous phase under reduced pressure to obtain compound 2; S3. First add compound 2 and triethylamine to anhydrous ether according to the molar ratio of compound 2, diethylphosphite chloride and triethylamine of 1:1.0-1.1:1.3-1.5, then add diethylphosphite chloride dropwise in an ice bath. After the addition is complete, keep the reaction warm for 2-3 hours. The completion of the reaction is detected by TLC, and the anhydrous ether is removed by rotary evaporation. Extraction is carried out with ethyl acetate and water, and the aqueous phase is concentrated under reduced pressure to obtain the modified compound.
5. The high elastic shoe material according to claim 1, characterized in that: In the preparation method of the composite antibacterial agent, the mass ratio of the carboxymethyl chitosan, the modified compound and the triethylamine is 1:0.2-0.3:0.05-0.
1.
6. The high elastic shoe material according to claim 1, characterized in that: The foaming agent is azodicarbonamide; the antioxidant is any one of antioxidant 5057, antioxidant 1135, and antioxidant 1010, or a mixture of several of them.
7. A process for preparing a high elastic shoe material according to any one of claims 1 to 6, characterized in that: The steps include: (1) adding thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, ethylene-octene copolymer and nitrile rubber into an internal mixer according to the mass ratio, and mixing at 160-170° C. for 5-8 minutes to obtain a premix; (2) adding a composite antibacterial agent, a foaming agent, zinc oxide, an antioxidant and a composite filler to the premix obtained in step (1), and kneading at 140-150° C. for 3-5 minutes to obtain a mixture; (3) The mixed material obtained in step (2) is granulated and placed in a mold for foaming to obtain a high-elastic shoe material.
8. The process for preparing a high elastic shoe material according to claim 7, characterized in that: The foaming conditions in step (3) are: foaming at 10-15 MPa, 170-180° C., for 30-40 minutes.
9. Use of the high elastic shoe material according to any one of claims 1 to 6 in shoe soles.
Citation Information
Patent Citations
Railway signal
CA106898A
Machine for casting lines of type
CA112185A
High-elasticity antibacterial foaming shoe material and preparation method thereof
CN117186625A
High-elasticity environment-friendly light comfortable foaming sole and preparation method thereof
CN117534948A
TPU composite material for high-performance automobile foot mat and preparation method thereof
CN112048168A